International financial market integration, asset compositions, and the falling exchange rate pass-through - Enders, Almira; Enders, Zeno; Hoffmann, Mathias (CESifo working papers, 2017)
This paper provides an explanation for the observed decline of the exchange rate pass-through into import prices by modeling the effects of financial market integration on the optimal choice of the pricing currency in the context of rigid nominal goods prices. Contrary to previous literature, we take the interdependence of this decision with the optimal portfolio choice of internationally traded financial assets explicitly into account. In particular, price setters move towards more local-currency pricing and portfolios include more foreign debt assets following increased financial integration. Both predictions are in line with novel empirical evidence.